Growth and Survival of Juvenile Giant Clam Tridacna squamosa as a Function of Density - Hasyim; Gunarto Latama; A. Niarti Ningsih; Inayah Yasir (Masyarakat Moluska Indonesia, 2019)
Juvenile Tridacna squamosa (less than 1 cm shell length) were placed in concrete trays in a coral habitat at the Marine Station of Hasanuddin University, Barang Lompo Island, South Sulawesi, Indonesia. A nylon net was used to protect against predators. The clams were stocked at 3 densities: 1000, 500, and 250 ind. m-2. Growth and survival were monitored in triplicate experiments. Growth was negatively correlated with density and significant differences were found between densities of 1000 and 250 ind m-2. After three months at the lowest density the mean shell length increment was 9 mm. There was no significant relation between density and survival rate.